1999
DOI: 10.1002/(sici)1097-4636(1999)48:2<159::aid-jbm10>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ultrahigh molecular weight polyethylene failure in artificial knee joints: Thermal effect on long-term performance

Abstract: The mechanism resulting in damage to and failure of ultrahigh molecular weight polyethylene (UHMWPE) tibial inserts was investigated on clinically retrieved components. The severity of the subsurface damage increased with the length of time that the component had been implanted. A theoretical analysis was developed to account for the generation of subsurface damage based on a heat transfer model. Friction generates surface heat during articulation of total knee systems. Due to the cooling effect of body fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This enhanced thermal diffusivity is due to the excellent reinforcing effect of the OH-BNNS on elastic modulus . In addition, an expectable 5% increase in the thermal conductivity (from 0.6198 to 0.6432 W/mK, apparently higher than ∼0.21–0.48 W/mK of the natural cartilages or other substitutes , ) was achieved for the OH-BNNS/PVA hydrogel with the introduction of only 0.12 wt% OH-BNNS, which agrees well with the parallel thermal conduction model (0.6464 W/mK as estimated, Supporting Information). Meanwhile, a significant 68% improvement in thermal conductivity was also observed for the OH-BNNS/PVA composite (dried) with 0.12 wt% OH-BNNS (Figure S8), which is comparable to or better than those of the previously reported BNNS/polymer composites. The more efficient heat transfer along the uniform thermal conductive network composed of OH-BNNS and PVA is attributed to the high thermal conductivity of OH-BNNS (as high as 360 W/mK for 11-layered h -BN) and strong hydrogen bonding interactions between the OH-BNNS and PVA chains .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…This enhanced thermal diffusivity is due to the excellent reinforcing effect of the OH-BNNS on elastic modulus . In addition, an expectable 5% increase in the thermal conductivity (from 0.6198 to 0.6432 W/mK, apparently higher than ∼0.21–0.48 W/mK of the natural cartilages or other substitutes , ) was achieved for the OH-BNNS/PVA hydrogel with the introduction of only 0.12 wt% OH-BNNS, which agrees well with the parallel thermal conduction model (0.6464 W/mK as estimated, Supporting Information). Meanwhile, a significant 68% improvement in thermal conductivity was also observed for the OH-BNNS/PVA composite (dried) with 0.12 wt% OH-BNNS (Figure S8), which is comparable to or better than those of the previously reported BNNS/polymer composites. The more efficient heat transfer along the uniform thermal conductive network composed of OH-BNNS and PVA is attributed to the high thermal conductivity of OH-BNNS (as high as 360 W/mK for 11-layered h -BN) and strong hydrogen bonding interactions between the OH-BNNS and PVA chains .…”
Section: Resultssupporting
confidence: 79%
“…Development of biocompatible, flexible, and hydrophilic cartilage substitutes is important to the replacement of diseased or damaged cartilages which lack ability to self-repair. To date, poly­(vinyl alcohol) (PVA) hydrogels with tissue-like viscoelasticity, high water contents (up to ∼90%), and superior lubricity have been the most promising candidates. ,, However, limited mechanical strength and poor toughness of the bare PVA hydrogels restrict their further applications for complex load bearing. ,,, In addition, local temperature increase upon cyclic physiological mechanical loading, resulting from the low heat transfer coefficient of the current cartilage substitutes, has always led to the mechanical failure and affected the normal metabolism of surrounding biotissues. As such, many efforts have been devoted to addressing the aforementioned drawbacks of the bare PVA hydrogels by incorporating nanomaterials. Recently, nanoparticles, such as hydroxyapatite, one-dimensional carbon nanotubes, , and especially effective two-dimensional graphene oxide (GO) ,, with larger specific surface area, have been introduced into the PVA hydrogels to enhance the mechanical strength and rigidity.…”
mentioning
confidence: 99%
“…Generally, the maximum is located about 1 to 2 mm below the surface in specimens subjected only to shelf‐aging and about 1 mm below the surface in specimens retrieved from patients after extended clinical use. It has been suggested that the formation of subsurface oxidation (white band) may be attributable to thermal effect during articulation in vivo ,44 fusion defect and calcium stearate,43 or an interactive reaction between the absorbed dose and an oxidant concentration (a theoretical analysis) 38…”
Section: Discussionmentioning
confidence: 99%
“…The success of total knee arthroplasty (TKA) for returning knee functionality has contributed to its widening application for treating diseases of the knee that have failed conservative treatments [ 1 ]. However, even with successive improvements in implant designs and materials, implant failure and patient dissatisfaction still persist [ 2 5 ]. Loosening of the implant is the most common reason for requiring a second TKA [ 6 8 ], which is reported to be linked to malalignment of the motion axis and the generation of wear particles which can induce osteolysis around the implant [ 9 10 ].…”
Section: Introductionmentioning
confidence: 99%